2019
DOI: 10.2478/sjecr-2019-0045
|View full text |Cite
|
Sign up to set email alerts
|

Exo-D-Mapps Attenuates Production of Inflammatory Cytokines and Promoted Generation of Immunosuppressive Phenotype in Peripheral Blood Mononuclear Cells

Abstract: Mesenchymal stem cells (MSCs) produce immunomodulatory factors that regulate production of cytokines and chemokines in immune cells affecting their functional properties. Administration of MSCs-sourced secretome, including MSC-derived conditioned medium (MSC-CM) and MSC-derived exosomes (MSC-Exos), showed beneficial effects similar to those observed after transplantation of MSCs. Due to their nano-size dimension, MSC-Exos easily penetrate through the tissue and in paracrine and endocrine manner, may deliver MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…In similar manner as Th1 cells, effector Th17 cells promote corneal epithelial barrier disruption through the enhanced production of IL-17 [15]. Since d-MAPPS efficiently attenuated production of IL-17 in activated CD4+ T helper cells [19], we assume that d-MAPPSinduced suppression of Th17 cell-driven inflammation in the eye was, at least partially, responsible for beneficial effects of d-MAPPS eye drops in DED patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In similar manner as Th1 cells, effector Th17 cells promote corneal epithelial barrier disruption through the enhanced production of IL-17 [15]. Since d-MAPPS efficiently attenuated production of IL-17 in activated CD4+ T helper cells [19], we assume that d-MAPPSinduced suppression of Th17 cell-driven inflammation in the eye was, at least partially, responsible for beneficial effects of d-MAPPS eye drops in DED patients.…”
Section: Discussionmentioning
confidence: 89%
“…Th1 cell-derived IFN-γ promote apoptosis and squamous metaplasia of the ocular surface epithelia while M1 macrophage-derived matrix metalloproteinases (MMPs) and inflammatory mediators (tumor necrosis factor alpha (TNF-α) and nitric oxide) disrupt epithelial cell barriers [15,18]. We recently demonstrated that d-MAPPS significantly attenuated concentration of IL-12 in the supernatants of activated human peripheral blood mononuclear cells (pbMNCs) and alleviate production of IFN-γ in activated lymphocytes [19]. d-MAPPS contains large number of immunoregulatory factors which are capable to suppress detrimental T cell-driven immune response [10].…”
Section: Discussionmentioning
confidence: 99%
“…d-MAPPS™ containing sTNFRI and sTNFRII binds to the TNF-α and prevent the TNF-α-dependent over-expression of E and P selectins on EC, crucially contributing to the reduced recruitment of circulating monocytes and lymphocytes in the uvea of d-MAPPS™-treated eyes [ 11 , 16 ]. Significantly attenuated concentrations of IL-12 and IFN-γ were observed in the supernatants of d-MAPPS™-treated monocytes and lymphocytes [ 12 ]. d-MAPPS™ containing GRO-γ is able to suppress DCs:T cell cross-talk and efficiently inhibits the DC-dependent generation of inflammatory Th1 cells [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Significantly attenuated concentrations of IL-12 and IFN-γ were observed in the supernatants of d-MAPPS™-treated monocytes and lymphocytes [ 12 ]. d-MAPPS™ containing GRO-γ is able to suppress DCs:T cell cross-talk and efficiently inhibits the DC-dependent generation of inflammatory Th1 cells [ 12 ]. GRO-γ-treated DCs had a tolerogenic phenotype characterized by the increased secretion of immunosuppressive IL-10, and reduced the production of inflammatory cytokines IL-12, IL-23, IFN-γ, and TNF-α [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation